Impact of brand equity and after-sales service on satisfaction and repurchase intention in a chinese heavy equipment brand - Ilman, Rizqin; Hudayah, Syarifah; Kuleh, J (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2026)
Customer retention is a critical issue in the business-to-business heavy equipment industry which is characterized by high investment value operational risk and long-term relational exchanges. This study aims to examine the effects of brand equity and after-sales service on customer satisfaction and their implications for repurchase intention in a Chinese heavy equipment brand operating in Samarinda Indonesia. A quantitative explanatory approach was employed using survey data collected from 120 corporate customers who are directly involved in purchasing decisions and equipment usage. Data were analyzed using SEM-PLS Modeling. The findings indicate that brand equity and after-sales service both enhance customer satisfaction however their influences on repurchase intention differ in mechanism. Brand equity does not directly affect repurchase intention but operates through customer satisfaction suggesting that brand-related perceptions must be validated by satisfactory post-purchase experiences. In contrast after-sales service influences repurchase intention both directly and indirectly through customer satisfaction highlighting the strategic importance of post-purchase support in reducing operational risk. Overall customer satisfaction emerges as a key mechanism linking brand and service-related factors to repurchase intention. This study provides practical insights for heavy equipment suppliers to prioritize service excellence and experiential validation of brand value to strengthen long-term customer relationships.